2004
DOI: 10.1007/s00464-003-8904-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of enteric fistulas

Abstract: Laparoscopic management of enteric fistula disease is safe and effective. Low morbidity and short hospital stay demonstrate the safety and benefit of the minimally invasive approach for even complicated fistula disease in patients with history of prior abdominal surgery and multiple fistulas, or in patients requiring multiple resections for fistulas from diverticular and Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Although few studies of open surgery have suggested that reoperation for CD recurrence is more challenging and complex than a primary resection [17], to our knowledge, only one study, including 16 patients, has been devoted to the role of laparoscopy in iterative surgery for CD recurrence [18]. Furthermore, two other studies including 10 and 16 patients respectively reported that laparoscopy could be feasible for this indication [15,19]. However, only one of these studies was comparative with a selected group of primary resections through laparoscopy, but it included no comparison with iterative surgery through the open approach [18].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Although few studies of open surgery have suggested that reoperation for CD recurrence is more challenging and complex than a primary resection [17], to our knowledge, only one study, including 16 patients, has been devoted to the role of laparoscopy in iterative surgery for CD recurrence [18]. Furthermore, two other studies including 10 and 16 patients respectively reported that laparoscopy could be feasible for this indication [15,19]. However, only one of these studies was comparative with a selected group of primary resections through laparoscopy, but it included no comparison with iterative surgery through the open approach [18].…”
Section: Resultsmentioning
confidence: 90%
“…Recently, several reports from experienced centers for both CD surgery and laparoscopy have shown that the laparoscopic approach could be feasible and safe for selected patients with a complicated form of CD including abscess and fistulizing disease [14][15][16]. Only few studies focused on reoperation for CD recurrence after a previous ileocolonic resection.…”
Section: Resultsmentioning
confidence: 98%
“…[16][17][18][19][20] In a study of 43 patients including 9 with colovesical fistula, Pokala et al reported less morbidity (11% versus 30.2% overall) in the colovesical fistula group. 20 Similar results have been reported for mixed diverticular fistulas (see Table 2), with morbidity ranging between 8% and 48%.…”
Section: Laparoscopic Managementmentioning
confidence: 99%
“…4,8,9 The outcomes of recent studies are difficult to interpret as many have incorporated both recurrent uncomplicated and complicated disease, have not differentiated between colovesical fistulas and other diverticular fistulas, [10][11][12][13][14][15] or have included fistulas of various aetiologies. [16][17][18][19][20] Other studies have not used a total laparoscopic approach but have performed technically challenging aspects with a resection-facilitated or hand-assisted technique. 4,[21][22][23] While these techniques improve operating times and preserve tactile feedback, their outcomes may not be comparable with a totally laparoscopic technique with intracorporeal suturing, and the inherent benefits of minimally invasive surgery are reduced.…”
mentioning
confidence: 99%
“…75 Repeated operation and ongoing inflammation also results in higher rates of conversion to laparotomy. 76 A recent meta-analysis looking at the use of laparoscopy in CD confirms its feasibility and safety. 77 In addition, recurrence of CD has not been found to be higher after laparoscopic ileocolic resection.…”
Section: Pyogenic Complications Of Intraabdominal CDmentioning
confidence: 88%